Hybrid Self-Powered Water Regulation for Residential Area - Che Omar, Nurul Nadhirah; Soomro, Dur Muhammad (Evolution in Electrical and Electronic Engineering, 2023)
Water is one of the greatest necessities for humans. The lack of water resources can affect the daily activities of people. Therefore, it is important that we as consumers should have a thrifty attitude without any waste of water. Water shortage also can be caused by damage to old water pipelines. This is due to the pressure of water flow in the pipeline. The higher the demand the more pressure will increase and cause the pipeline to leak. Therefore, this study has been conducted to create a water distribution system according to the capacity that has been set for an individual which is 160 litres per person per day. Water will regulate the same amount of water in the residential houses. This system uses mini hydroelectric energy which will generate electricity by itself through the flow of water in the pipeline. This electrical energy will also turn on the solenoid valve that functions as an open and closed for the water to flow to the tank. The water tank for each house is measured by the capacity of the occupants of a house. The volume of water is measured using a water detection device to measure the water in the house tank. The water level will also be measured using an ultrasonic sensor to detect the distance and to give a signal to the solenoid valve to close the water pipe.